Study on Smoke Characteristics in Cavern Complexes of Pumped-Storage Power Stations - Peifeng Hu; Tong Xu; Chang Liu; Kai Wang; Fazheng Chong; Fengju Shang; Jiansong Wu (Fire)
The underground power houses of pumped-storage power stations (PSPSs) are highly complex, with interconnected and multidimensional structures, including various tunnels, such as the main and auxiliary power houses (MAPH), main transformer tunnel (MTT), tailrace gate tunnel (TGT), access tunnels (ATs), cable tunnels (CTs) etc. During intensive civil construction and electromechanical installation, fire risk becomes particularly prominent. Current research mainly examines fire incidents within individual tunnels, lacking comprehensive analyses of smoke spread across the entire cavern network. Therefore, in this study, a numerical model of a cavern complex in a PSPS was established to analyze smoke behavior and temperature distribution under various fire scenarios. The results indicated that when a fire occurred in the MAPH, the fire risk was relatively higher compared to fires in other places. Using the example of smoke spread from the MAPH to the MTT, the smoke spread process through key connecting caverns was analyzed. Initially, the temperature and velocity were stable, and the CTs and traffic cable tunnel in the auxiliary powerhouse (TCTAP) were the main smoke paths. After 7 min, the heat release rate (HRR) became stable, and CTs and ATs became the main paths for smoke spread, which could provide a reference for improving fire design in underground cavern systems.